WORK ON THE TEXT (Academia Science Repository, 2023)
Existing texts in textbooks created on the basis of the communicative method differ from old textbooks in terms of authenticity. Texts in old textbooks would have been written only by textbook authors. The concept of "authentic text means an or iginal and an exact written or oral copy.